New tool to help decision making in civil engineering - Castillo, Enrique; Lozano-Galant, Jose Antonio; Nogal, Maria; Turmo, Jose (Journal of Civil Engineering and Management, 2015)
Structural collapses have indirectly produced important progress in science. The last lesson learnt from structural collapses reveals the important role of polyrational systems of equations in the Civil Engineering field, as all problems in Physics and Engineering involving scale variables lead to systems of these equations. Since no efficient methods are known to solve this type of equations, a powerful and efficient method to multivariate polyrational equations using observability techniques is presented in this paper. It is pointed out that this method can be applied to solve different Civil Engineering problems. The information obtained by this tool can be used to assist decision making and risk management processes during maintenance and service life. As an example of its use, a structural damage detection problem is solved.